An Investigation of the Ventilation Systems of Whole-Indoor Urban Substations - Dakun Xu; Lei Zhang; Hao Wang; Kangyue Wang; Wenke Zhang (Buildings)
The electricity load increases significantly with the development of the economy, which raises the issue of scarce land resources; therefore, the application of whole-indoor urban substations has become more and more extensive. However, both the closed environment of indoor substations and their unreasonable ventilation systems mean that the heat dissipation of the equipment cannot be discharged in time. In this study, a combination of natural and mechanical ventilation systems is developed to solve the problem of high indoor temperatures, and corresponding studies are conducted via both numerical simulation and experimental research. Firstly, the ventilation and heat dissipation problem of the whole-indoor urban substation was investigated using numerical simulation technology, and then the feasibility of the ventilation system was determined. Secondly, the experimental platform (including the heat dissipation equipment and ventilation system) was set up, the heat dissipation of the reactor room was analyzed, and the system was tested experimentally. Afterward, the noise generated by the experimental platform was measured and predicted. Finally, via the numerical simulation analysis, it was found that the ventilation effect would be improved regardless of the heat dissipation and that reducing the outdoor temperature or increasing the ventilation volume would reduce the indoor temperature, which could be controlled within 40 °C. The results of this study provide a reference basis and technical guidance for the engineering projects of ventilation systems for indoor substations, which can effectively solve the problem of excessive indoor temperature caused by heat dissipation from substation equipment while providing a favorable guarantee for sustainable operation of the substation.